2015
DOI: 10.1515/hukin-2015-0113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Regular Recreational Exercise Training on Serum ANGPTL3-Like Protein and Lipid Profile in Young Healthy Adults

Abstract: Evidence of the role of ANGPTL3, a liver-secreted glycoprotein, in serum lipid turnover, led us to hypothesize that this protein may be involved in modification of the lipid profile induced by exercise-training. Given the lack of data regarding this issue, the main goal of the present study was to investigate the effects of regular participation in a recreational physical activity program on serum ANGPTL3 and selected lipid profile measures in young, apparently healthy female and male adults. We compared serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Correlation and regression analyses (see Table 5 and Table 6 ) showed that patient gender and age may be associated, to some extent, with ANGPTL-3 and ANGPTL-4 levels during HCV infection or after HCV eradication. Such relationships have been described in studies concerning healthy populations [ 76 , 77 ]. They may be due to the higher activity of target lipases LPL and HL seen in women or reflect inherent changes in lipid metabolism occurring with age [ 78 ].…”
Section: Discussionmentioning
confidence: 91%
“…Correlation and regression analyses (see Table 5 and Table 6 ) showed that patient gender and age may be associated, to some extent, with ANGPTL-3 and ANGPTL-4 levels during HCV infection or after HCV eradication. Such relationships have been described in studies concerning healthy populations [ 76 , 77 ]. They may be due to the higher activity of target lipases LPL and HL seen in women or reflect inherent changes in lipid metabolism occurring with age [ 78 ].…”
Section: Discussionmentioning
confidence: 91%
“…To our knowledge, the impact of acute exercise or chronic exercise on ANGPTL3 expression has not been studied. A cross-sectional study of 22 physically active students and 28 age-matched sedentary students found no difference in serum ANGPTL3 between the groups ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity No significant differences were observed related to physical activity status. 48 Serum ANGPTL3 levels are not influenced by physical activity status.…”
Section: Factors Influence Commentsmentioning
confidence: 94%
“…36 Sex Women have higher serum ANGPTL3 compared with men. 48 Serum ANGPTL3 levels have high inter-individual variability.…”
Section: Factors Influence Commentsmentioning
confidence: 99%